The form and thematic content of #Lori Iro as social media autobiographical novel - Onyekachi Peter Onuoha; Angela A Ajimase (Center for Humanities and Innovation Studies, 2022)
The digital space expands our perception of the autobiographical Novel's form in the twenty-first century. Through the application of the concept of form and themes, this paper submits that #Lori Iro is a social media autobiographical novel and exists in multimodal forms across multi social media platforms. This paper observes that social media autobiographical novel is the contribution of Nigerian netizens in the further development of The African Novel. This study observes that the social media autobiographical novel like #Lori Iro is told by multiple narrators, which thrives on auto-fiction linking narratives through (#) hashtags which are fiction as plot development and pagination within the digital apps.